Revitalization of Regional Potential in The Efforts to Develop Tourism Villages (Case Study in Kebon Ayu Village, West Lombok) - Lestari, Aprilia Dinda (West Science Social and Humanities Studies, 2025)
This study aims to obtain an overview of the influence of revitalization in efforts to develop tourist villages in relation to the potential of the area in Kebon Ayu Village, Gerung District, West Lombok. The analysis technique used in this study is the SWOT analysis (Strengths, Weaknessess, Opportunities, and Threats) to systematically identify various factors in order to achieve the strategy. The results of the study indicate that Kebon Ayu Village has great tourism potential thanks to its rich culture, history, and natural beauty. To achieve optimal development of tourist villages, a comprehensive strategy is needed that includes increasing the capacity of human resources (HR), building cooperation networks, and utilizing natural and cultural potentials sustainably and building a unique identity as well as strengthening the branding of tourist villages.